Approaching Algerian Media Law 23-14 in Light of the Principles of Social Responsibility Theory - An Analytical Study - عبد الرحمان باباواعمر (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
The study aims to highlight the manifestations of the principles of social responsibility theory of Algerian media in Organic Law 23-14, dated August 27, 2023, related to media, through an analytical study of the provisions included in this law. The study found an embodiment of the duality (freedom - responsibility) in most articles of the law. This indicates a clear tendency of the Algerian legislator towards this theory in drafting the new media law, while noting some deviations from the principles of the theory and limitations on media practice freedom.